Les « retombées » des évènements sportifs sont-elles celles que l’on croit ? - Patrice Bouvet (Revue de la Régulation)
The theory of multipliers lays on 2 fundamental hypotheses: Saving a part of the newly invested income and keeping the income spent. In the theory of the monetary circuit perspective, rejecting these two hypotheses enable to provide a new explanation of the winner’s curse. After studying the financial impact of major sports events, many countries apply for the organizations of these events. According to us, the interest of applying is widely debatable. However there should be many applicants in the years to come.